2017
DOI: 10.2298/jas1704423k
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of farmers to extension trainings in Nigeria: Implications for adoption of improved agricultural technologies in Ogun state southwest region

Abstract: In Africa, the outcome of development research is enormous and its dissemination has had a huge impact, especially in Nigeria for the last few decades. This impact is observable in the adoption of innovation by farmers with the aim of transforming agricultural production. To enhance adoption, training of the farmers is required. However, the attitude of farmers towards training could influence their decision on the uptake of agricultural innovation. The purpose of this study was to evaluate whether the attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…This indicates that the exhibition of a positive attitude by the extension agents will also likely result in them having a positive perception of the effects of extension professionalization on service delivery. This is in agreement with the findings of Kazeem et al (2017) that attitude exerted a positive influence on perceived effect or usefulness of an innovation.…”
Section: Determinants Of Perceived Effects Of Extension Professionalisupporting
confidence: 93%
“…This indicates that the exhibition of a positive attitude by the extension agents will also likely result in them having a positive perception of the effects of extension professionalization on service delivery. This is in agreement with the findings of Kazeem et al (2017) that attitude exerted a positive influence on perceived effect or usefulness of an innovation.…”
Section: Determinants Of Perceived Effects Of Extension Professionalisupporting
confidence: 93%
“…Consequently, farmers’ problems are not being adequately captured, not being addressed, and often it takes far too long to get a resolution for their problem. Kazeem et al (2017) found that while farmers’ attitudes towards training were positive, the content was often not relevant to the rural farmers’ problems or presented to accommodate their perspectives. Other researchers found even with well-intentioned food security-related regulations or third-party certification, there was difficultly reaching the rural individuals in countries like Nigeria (Clark and Hobbs, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Clark and Hobbs, 2018), but academic advice does not work in Nigeria unless it is data-driven and customized by local experts to accommodate the unique sociocultural issues (Olawuyi, 2019; Omotayo et al, 2018; Strang et al, 2019). The common factors empirically found to impact food security in Nigeria include arable land size, modern inputs, education level, family size, age, technology use, farmer attitude and income diversification (Abu and Soom, 2016; Akeju et al, 2018; Kazeem et al, 2017; Mogues and Olofinbiyi, 2018; Obayelu et al, 2019; Okunold et al, 2018; Olawuyi, 2019; Olowogbon et al, 2019). Unfortunately there are very few forward-looking studies, and no solutions have been published, to resolve the food security crisis in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, practice is a matter of understanding what was planned (Hassan et al, 2019). According to the findings of Kazeem et al (2017), farmers demonstrated a higher level of adoption of innovation as a result of the practical demonstrations provided during the training. Other relevant studies on farmers' practice of technology adoption offer different perspectives.…”
Section: Practice Toward Organic Fertilizer Adoptionmentioning
confidence: 99%